A STUDY OF BASIC IMMUNIZATION SERVICES FOR CHILDREN AS THE GOVERNMENT'S RESPONSIBILITY IN PROVIDING HEALTH SERVICES IN THE CITY OF PALU - Fitra Kemalasari (TADULAKO MASTER LAW JOURNAL, 2024)
​This research aims to determine and analyze the government's efforts to fulfill children's rights to basic immunization. Conceptually, human rights contained in Pancasila accommodate aspects of humans as individual and social creatures. Health Law Number 17 of 2023 article 44 paragraph 2 states that every baby and child have the right to receive immunization to provide protection. Immunization is carried out to prevent diseases that can be prevented by immunization. This research uses empirical legal research with qualitative analysis methods. The research results show that the government's first efforts are to provide free vaccinations, increase vaccine availability and immunization coverage, seek to add 3 types of vaccines and the government is also actively conducting campaigns and training to increase public awareness. In Palu City, if the targets set are not met, the person in charge of the program will take action by carrying out a sweep to ensure that all toddlers can get their right to complete basic immunization. Second, the implementation of immunization has been carried out in accordance with operational standards involving competent workforce and promotion in the form of counseling has been carried out optimally so that the majority of the community understands the importance of basic immunization for children. However, there are still obstacles regarding the mindset of people who refuse immunization based on an understanding of the long-term function of immunization for children.